Biological phenotypes underpin the physio‐somatic symptoms of somatization, depression, and chronic fatigue syndrome. (17th August 2013) - Anderson, G.; Berk, M.; Maes, M.
<x xml:space="preserve">Abstract</x> Objective Somatization is a symptom cluster characterized by 'psychosomatic' symptoms, that is, medically unexplained symptoms, and is a common component of other conditions, including depression and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). This article reviews the data regarding the pathophysiological foundations of 'psychosomatic' symptoms and the implications that this has for conceptualization of what may more appropriately be termed physio‐somatic symptoms. Method This narrative review used papers published in PubMed, Scopus, and Google Scholar electronic databases using the keywords: depression and chronic fatigue, depression and somatization, somatization and chronic fatigue syndrome, each combined with inflammation, inflammatory, tryptophan, and cell‐mediated immune (CMI). Results The physio‐somatic symptoms of depression, ME/CFS, and somatization are associated with specific biomarkers of inflammation and CMI activation, which are correlated with, and causally linked to, changes in the tryptophan catabolite (TRYCAT) pathway. Oxidative and nitrosative stress induces damage that increases neoepitopes and autoimmunity that contribute to the immuno‐inflammatory processes. These pathways are all known to cause physio‐somatic symptoms, including fatigue, malaise, autonomic symptoms, hyperalgesia, intestinal hypermotility, peripheral neuropathy, etc. Conclusion Biological underpinnings, such as immune‐inflammatory pathways, may explain, at least in part, the occurrence of physio‐somatic symptoms in depression, somatization, or myalgic encephalomyelitis/chronic fatigue syndrome and thus the clinical overlap among these disorders.